2018
DOI: 10.1016/j.preteyeres.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The pupillary light responses of animals; a review of their distribution, dynamics, mechanisms and functions

Abstract: The timecourse and extent of changes in pupil area in response to light are reviewed in all classes of vertebrate and cephalopods. Although the speed and extent of these responses vary, most species, except the majority of teleost fish, show extensive changes in pupil area related to light exposure. The neuromuscular pathways underlying light-evoked pupil constriction are described and found to be relatively conserved, although the precise autonomic mechanisms differ somewhat between species. In mammals, illum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
103
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(113 citation statements)
references
References 325 publications
(640 reference statements)
5
103
2
Order By: Relevance
“…While it has been suggested that pupils may aid in camouflaging the eye (Muntz, 1977;Douglas 2018;Douglas et al, 1998;, this has never been tested experimentally. The two experiments reported here present evidence that the elaborate pupil shape of the skate Leucoraja erinacea may indeed serve a camouflage function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While it has been suggested that pupils may aid in camouflaging the eye (Muntz, 1977;Douglas 2018;Douglas et al, 1998;, this has never been tested experimentally. The two experiments reported here present evidence that the elaborate pupil shape of the skate Leucoraja erinacea may indeed serve a camouflage function.…”
Section: Discussionmentioning
confidence: 99%
“…Most pupils respond to light by constricting. This carefully regulates the amount of light entering the eye and it is a crucial component in optimizing resolution and sensitivity in the retina (Wilcox and Barlow, 1975;Hammond and Mouat, 1985;Land and Nilsson, 2012;Douglas 2018). A round, dilated pupil is often a very conspicuous structure that stands out, possibly giving away the location of a lurking predator, or camouflaging prey animal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To test whether this effect reflects a common sensorimotor strategy across species, we conducted experiments in humans and macaque monkeys. While the brainstem circuit for the PLR is preserved between these two species [11], there are systematic differences in pupil dynamics between monkeys and humans [12], and it is unclear whether the pupil is under the same amount of cortical/cognitive control.…”
Section: Introductionmentioning
confidence: 99%